The Impact of the Trade War Between the United States and China on ASEAN and Huawei Technologies as Reviewed by Trade, Investment, and Competition Law - Jessica Natalia Widjaja (Universitas Pelita Harapan, 2022)
The Trade War between the United States and China is impacting the worldwide economy, especially ASEAN part nations. The aim of this paper is to look at the effect of the US-China exchange battle on ASEAN and Huawei Technologies. It is separated into four sections: the initial segment will clarify the idea of worldwide exchange as it is analyzed by profession, speculation, and rivalry law, the subsequent part will clarify the exchange battle between the US and China as it influences ASEAN and Huawei Technologies, and the third part will clarify the job of RCEP as a guide to ASEAN and Huawei Technologies. The result of the analysis shows that the exchange battle between the US and China can be settled by building up an unbiased association as the Regional Comprehensive Economic Partnership (RCEP), and that substantial advances can be taken to lessen dependence on the US and China by diminishing commodities and imports, just as expanding and working on the quality of domestic items.